PENGEMBANGAN MANAJEMEN KINERJA PERAWAT DAN BIDAN SEBAGAI STRATEGI DALAM PENINGKATAN MUTU KLINIS = PERFORMANCE MANAGEMENT DEVELOPMENT FOR NURSES ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Pengembangan Manajemen Kinerja/PMK (Performance Management Development) becomes a national strategy for improving quality of clinical care, especially for nursing and midwivery care. As a strategy for improving clinical care quality, PMK implementation are therefore, should be reviewed within the clinical governance framework. Objective: To review the PMK implementation based on the clinical governance framework as a national strategy for improving quality in clinical care either in hospital or puskesmas. Methods: Review the conceptual background of PMK, and the results of the evaluation study of PMK implementation in Magelang, Purworejo, and Cilacap districts, within the clinical governance framework. Result: Pengembangan Manajemen Kinerja (PMK) is a rapid and appropriate strategy for improving quality of clinical care within a clinical governance framework in the clinical care micro system when it is integrated in the existing quality system. Pengembangan Manajemen Kinerja (PMK) is very beneficial for the nurses and midwives in improving their quality of care, even though the benefit for the patient has yet to be evaluated. Pengembangan Manajemen Kinerja (PMK) provides basic foundation for the implementation of clinical governance when it is implemented based on the original model. Strong emphasis should be given to the advocacy to stakeholders to get supports and commitment, and on the followed up phase by planned and established coaching and monitoring system. Conclusion: As a national strategy for improving clinical care especially nursing and midwivery care, PMK is a simple and appropriate strategy for improving quality of clinical care, PMK can be viewed as initial strategy for the implementation of clinical governance. Keywords: clinical governance, performance management, clinical care, clinical quality